2010
DOI: 10.1016/j.jbiomech.2010.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of registration on cyclical kinematic data

Abstract: Given growing interest in Functional Data Analysis (FDA) as a useful method for analyzing human movement data, it is critical to understand the effects of standard FDA procedures, including registration, on biomechanical analyses. Registration is used to reduce phase variability between curves while preserving the individual curves shape and amplitude. The application of three methods available to assess registration could benefit those in the biomechanics community using FDA techniques: comparison of mean cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
0
37
1
3
Order By: Relevance
“…Because a common time interval is required for FDA analyses, it is important to assess whether registration procedures are necessary after standard time normalization has been applied to the data. Crane et al (2010) found that registration after time normalization may not always be necessary. They concluded that when obtaining an average curve was the purpose of registration, the additional alignment did not affect the interpretation of the behavior enough to warrant the additional data manipulation.…”
Section: Is Time Normalization Necessary?mentioning
confidence: 99%
See 2 more Smart Citations
“…Because a common time interval is required for FDA analyses, it is important to assess whether registration procedures are necessary after standard time normalization has been applied to the data. Crane et al (2010) found that registration after time normalization may not always be necessary. They concluded that when obtaining an average curve was the purpose of registration, the additional alignment did not affect the interpretation of the behavior enough to warrant the additional data manipulation.…”
Section: Is Time Normalization Necessary?mentioning
confidence: 99%
“…So when might registration be useful? When specific functional data analyses, such as those discussed in Section 4, will be used, Crane et al (2010) found that decreases in inter-subject variability within homogenous groups indicate registration may be justified. Because of this, when functional data analyses are used, registration improves the likelihood of finding significant differences between two or more populations, if they indeed exist.…”
Section: Is Time Normalization Necessary?mentioning
confidence: 99%
See 1 more Smart Citation
“…joint angle) are usually reduced to a single/few discrete measure(s) that purportedly represent a joint's movement technique (e.g. peak flexion), but in reality comprises less than 2% of the available data [17], [18]. 2.…”
mentioning
confidence: 99%
“…mean ±95% confidence intervals) [10]. However, this may result in a distortion of the data as key events are not time aligned across trials [18].…”
mentioning
confidence: 99%